Desvendando características biológicas e moleculares dos vírus gigantes: predição e análise de motivos promotores em Marseillevírus, Faustovírus e Kaumoebavírus e caracterização do efeito citopático do Tupanvírus em Acanthamoeba castellanii. - Graziele Pereira Oliveira (2018)
The discovery of giant viruses led to the breakdown of paradigms in virology field due virus particle size and genomic and structural complexity. In the last decade, the search for new giant viruses intensified leading to the discovery of marseillevirus, faustovirus, kaumoebavirus and tupanvirus. In order to elucidate the biological and molecular informations of these viruses that remain unclear, this work aimed to predict and analyze the promoter motifs in Marseilleviridae family viruses, in faustovirus and kaumoebavirus, further to characterize the cytopathic effect of tupanvirus in Acanthamoeba castellanii. The analysis of promoter motifs led to the first characterization of an octamer (AAATATTT) that can act as a promoter in the Marseilleviridae family. The distribution and localization of the motif relative to the start codon followed a pattern similar to that demonstrated for other promoters described among NCLDV members. In addition, the biological relevance of the predicted octamer was demonstrated and the motifs repetitions in intergenic regions of the marseillevirus genome was associated with the high ability of the marseillevirus to acquire genes by lateral gene transfer contributing to explain their mosaicism and genomic plasticity. The search for promoter motifs in faustovirus and kaumoebavirus revealed that these viruses share in abundance the same promoter sequences (TATTT and TATATA), as previously described in viruses of the Asfarviridae family. It has been demonstrated that the predicted motifs are present in more than 65% of the genes shared among faustovirus, kaumoebavirus and asfarvirus, reinforcing the phylogenetic relationship between these viruses. In addition to the regulation of transcriptional processes, an important challenge for viruses in nature is the search for host cells. In this context, we performed a detailed characterization of the cytopathic effect of tupanvirus in the culture of Acanthamoeba castellanii, which led to the description of a new type of virus-host interaction involving the tupanvirus. Tupanvirus infection has been shown to be capable of inducing the expression of genes encoding a viral and cellular mannose binding protein (MBP), suggesting the importance of the MBP in tupanvirus multiplication cycle. Interestingly the presence of mannose led not only to suppression of the increase in transcripts level of the viral and cellular MBP genes, but also led to the inhibition of amoebal-bunches formation at a concentration dependent, suggesting that the bunches formation correlates with the expression of the viral and cellular MBP genes. Finally, we demonstrate that the amoebal-bunches formed during multiplication of tupanviruses are able to interact with uninfected cells contributing to viral spread.